Machine learning in cancer research with applications in colon cancer and big data analysis - Lu, Zhongyu, 1955- (Advances in medical technologies and clinical practice book series., 2021)
"This book presents a general picture for the latest research output and the state of the art technology in the bioinformatics in cancer research, and big data, machine learning theory and technologies in the various applications"--